KEPASTIAN HUKUM BAGI PEMEGANG HAK CIPTA ATAS ROYALTI PEMUTARAN LAGU UNTUK KEPENTINGAN KOMERSIAL DI CAFE - Putri, Kadek Githa Nirmala; Putra, Made Aditya Pramana (Kertha Negara : Journal Ilmu Hukum, 2023)
Royalties are rewards that creators receive for their creations. Examining legal protection for creators for the use of their works in the form of songs for commercial purposes in cafes is part of the purpose of this study. In this research, a statutory research approach is used which is also called normative legal research. The result is preventive and repressive protection given to the creator of the royalties he created. Legal consequences if the work is used for commercial purposes, it will be charged royalty payment obligations to the party. Keywords: Legal Protection, Copyright, Copyright Holder, Royalties